Pain sensitivity in patients with haemophilia following moderate aerobic exercise intervention. (11th July 2016) - Krüger, S.; Weitz, C.; Runkel, B.; Hilberg, T.
Abstract : Background: Physical activity is influenced by pain and vice versa. Although studies recommend exercise therapy for patients with haemophilia (PwH), the influence of physical activity on the pain condition in PwH has not been investigated so far. Aim: Aim of this study was to examine the effect of a treadmill intervention with self‐chosen velocity on the acute pain sensitivity in PwH. Patients and methods: Twenty PwH [aged 24–58 years, moderate ( n = 3) to severe ( n = 17) haemophilia A ( n = 17) or B ( n = 3)] and 20 control subjects (aged 26–61 years) were included in this study. Eighteen PwH and all controls completed a treadmill intervention for 30 min. Pressure pain thresholds (PPT) in Newton (N) were measured at both the knees, ankles and elbows, sternum and forehead before (pre) and immediately after walking (post). Results: PwH and controls walked with comparable speed (mean speed in km h −1 ; PwH: 3.5, controls: 3.8), resulting in significantly different values of performance‐related parameters such as heart rate (mean heart rate per minute; PwH: 102, controls: 86; P ≤ 0.01). Compared to baseline values, PPT remained unaltered at all landmarks in both groups after walking (e.g. pre/post in Newton; knee right: PwH: 63.1/63.0, controls: 93.8/93.8; left knee: PwH: 62.1/62.7, controls: 90.0/93.4), indicating a non‐increasing pain condition. Conclusion: Findings of unaltered PPT following moderate aerobic exercise showed initial evidence that PwH are able to perform an endurance exercise with self‐chosen velocity for 30 min as recommended, without increasing the acute pain condition. By doing so, PwH can benefit from the positive effects of endurance exercise.